Unraveling the causal relationship between serum minerals and pancreatic cancer: a Mendelian randomization study - Cong Liu; Huajun Wu; Dongdong Cai; Xin Yu (Discover Oncology)
Abstract Background Pancreatic cancer is among the most lethal malignancies, characterized by a poor prognosis and limited modifiable factors. Emerging evidence indicates that serum mineral levels may influence the likelihood of developing pancreatic cancer. However, the causal relationship between serum minerals and pancreatic cancer remains unclear and warrants further investigation. Methods This Mendelian randomization (MR) study was conducted to explore the causal effects of serum mineral levels on pancreatic cancer risk. Genetic variants associated with serum mineral levels, including calcium, iron, magnesium, zinc, selenium, and copper, were selected as instrumental variables (IVs) from large-scale genome-wide association study (GWAS) data. Multiple methods, including inverse variance weighting (IVW), MR-Egger, weighted median, weight methods, were employed to perform MR analysis. The effect sizes from the MR analysis, using two independent GWAS summary datasets related to pancreatic cancer, were combined through meta-analysis. The Cochrane Q test, MR-Egger intercept test, MR-PRESSO global test, and leave-one-out test were conducted for sensitivity tests. Results Our MR analysis demonstrated a significant causal effect of genetically predicted serum calcium levels on increased pancreatic cancer risk [OR = 1.64, 95% CI 1.05–2.57, P = 0.029 (discovery cohort); OR = 1.52, 95% CI 1.07–2.15, P = 0.019 (validation cohort)], while no significant associations were found for other serum minerals (P > 0.05). Additional meta-analysis reinforces and substantiates this conclusion (pooled OR = 1.56, 95% CI 1.19–2.06, P = 0.001). No evidence of pleiotropy or heterogeneity was detected across multiple sensitivity tests (P > 0.05). Conclusion This study provides new evidence supporting the causal role of certain serum minerals, particularly calcium, in the development of pancreatic cancer. These findings may help inform future research into preventive strategies or therapies aimed at modulating mineral levels in patients at high risk of pancreatic cancer.